PERANCANGAN DAN IMPLEMENTASI SISTEM MANAJEMEN DALAM PENGELOLAAN DATA AKADEMIK BERBASIS WEB DI SMA NEGERI 1 LIWA - Aldo Pradipta; Machudor Yusman; Dewi Asiah Shofiana; Aristoteles Aristoteles (Jurnal Pepadun, 2021)
SMA Negeri (SMAN) 1 Liwa is a secondary education school located in the West Lampung Regency of Lampung Province. The current management of academic data in SMA Negeri 1 Liwa still implements manual methods. Thus, this research is conducted to build a web-based academic data management system for SMA Negeri 1 Liwa. It aims to digitally process administrative data, such as the data of lessons, students, teachers, classes, mutations, and student grade reports. The infamous waterfall method was applied to develop the system with the PHP and MySQL programming languages. Performance of the system was examined using the black-box testing method. From this study, a web-based system was successfully developed and can be accessed directly by the teachers and administrative staff.